PENINGKATAN PRODUKSI KOMPOS DENGAN MESIN PENCACAH SAMPAH ORGANIK DI DESA BADEAN KECAMATAN BLIMBINGSARI - Mukhtar, Anas; Eko Musantono, Agus; Mulyadi, Adi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The increase in composition production in Desa Badean, Kecamatan Blimbingsari, is a strategic approach to effectively manage environmental degradation and waste disposal. One of the most important aspects of producing compositions is the processing of organic matter, which requires a significant amount of time and effort. The purpose of this Community Service Program is to increase the productivity and efficiency of composition production by using an organic solvent extraction method. This machine is designed to speed up the organic matter degradation process so that raw materials for composites can be produced more quickly and accurately. The results of implementing the shredding machine are thought to show a significant increase in the volume of compost produced. In addition, the produced composition quality is also higher due to more homogeneous particle size. It is hoped that through the advancement of technology, the composition industry in Desa Badean would continue to grow and benefit the local economy and environment. The compost production capacity of the Community Self-Help Group (KSM) in Badean Village, Blimbingsari Sub-district, Banyuwangi Regency is not balanced with the daily increase in waste. KSM is only able to process organic waste with a machine capacity of ±50 kg per day. Thus, the design of an organic waste shredding machine is applied to increase production capacity. The machine design is proposed based on compost production needs with specifications of frame (91 cm long, 46.5 cm wide, 67 cm high), drum (36 cm diameter, 51 cm long), shaft (1 inch diameter, 75 cm long), and hopper (30 cm long, 30 cm wide, 28 cm high). The results of the application of the shredder can increase the compost production capacity for KSM partners by ± 85-100 kg per day.